Strategies used by Nurses regarding the quick reagent test for syphilis in pregnant women - Muller, Érico Acosta (2020)
Objective: to know the strategies used by nurses in face of the rapid reagent test for syphilis in pregnant women. Methodology: qualitative study, with eight nurses from health units in a city in the interior of Rio Grande do Sul, who responded to a semi-structured interview that contemplated questions about care for pregnant women based on a rapid test result that is reactive to the syphilis. Content analysis was used. Results: three categories were constructed: Permanent health education as a care strategy in primary health care; Health education as a promoter of the pregnant woman's self-care and autonomy; Strategies for the improvement and access to procedures / actions by health teams, weaknesses are perceived by not following protocols. Conclusions: nurses are prepared to carry out rapid tests, however, in view of the reactive test, the decision making of actions is heterogeneous.